Non‐separable multivariate filter banks from univariate wavelets. Issue 10 (8th February 2013) - Chen, Qiuhui; Ren, Guangbin; Cerejeiras, Paula; Kaehler, Uwe
Abstract: The main purpose of this paper is the design of multivariate filter banks starting from univariate wavelet filters. The matrix completion is solved by utilizing some special Toeplitz matrices. A generalized method of rational polynomial univariate filter with preset zero points set is constructed.